Biodesign : the process of innovating medical technologies - Zenios, Stefanos; Makower, Josh; Brinton, Todd J.; Kumar, Uday N.; Watkins, F. T. Jay (Cambridge ; New York : Cambridge University Press, 2015)
'This step-by-step guide to medical technology innovation, now in full color, has been rewritten to reflect recent trends of industry globalization and value-conscious healthcare. Written by a team of medical, engineering, and business experts, the authors provide a comprehensive resource that leads students, researchers, and entrepreneurs through a proven process for the identification, invention, and implementation of new solutions. Case studies on innovative products from around the world, successes and failures, practical advice, and end-of-chapter'Getting Started' sections encourage readers to learn from real projects and apply important lessons to their own work. A wealth of additional material supports the book, including a collection of nearly 100 videos created for the second edition, active links to external websites, supplementary appendices, and timely updates on the companion website at ebiodesign.org. Readers can access this material quickly, easily, and at the most relevant point in the text from within the ebook'--Provided by publisher.
Machine generated contents note: Preface; Focus on value; Global perspectives; Process insights; Part I. Identify: Stage 1. Needs Finding: 1.1 Strategic focus; 1.2 Needs exploration; 1.3 Need statement development; Case study; Stage 2. Needs Screening: 2.1 Disease state fundamentals; 2.2 Existing solutions; 2.3 Stakeholder analysis; 2.4 Market analysis; 2.5 Needs selection; Case study; Part II. Invent: Stage 3. Concept Generation: 3.1 Ideation; 3.2 Initial concept selection; Case study; Stage 4. Concept Screening: 4.1 Intellectual property basics; 4.2 Regulatory basics; 4.3 Reimbursement basics; 4.4 Business models; 4.5 Concept exploration and testing; 4.6 Final concept selection; Case study; Part III. Implement: Stage 5. Strategy Development: 5.1 IP strategy; 5.2 R&D strategy; 5.3 Clinical strategy; 5.4 Regulatory strategy; 5.5 Quality management; 5.6 Reimbursement strategy; 5.7 Marketing and stakeholder strategy; 5.8 Sales and distribution strategy; 5.9 Competitive advantage and business strategy; Case study; Stage 6. Business Planning: 6.1 Operating plan and financial model; 6.2 Strategy integration and communication; 6.3 Funding approaches; 6.4 Alternate pathways; Case study; About the author team; Image credits; Glossary; Index.
Includes bibliographical references and index.
Keywords: Biomedical Engineering -- organization & administration; Biomedical Technology